DIALOG BIMBINGAN DAN KONSELING PERSPEKTIF AL-ASR AYAT 3 - Marsal Yunas Muliadi; Irman Irman (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2023)
The study of dialogue in counseling is the main factor in the counseling process which contains positive values that are transferred to clients. The purpose of this study is to describe dialogue in counseling guidance that will be discussed in accordance with the perspective of Al –Asr Paragraph 3. The research method used in this research is the study of literature. The results of the study show that dialogue in guidance and counseling is in accordance with the principles in Al-Asr verse 3, namely